2021
DOI: 10.1002/chem.202004366
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Cross‐Linking of 2H‐MoS2 Nanosheets

Abstract: The combination of 2D materials opens a wide range of possibilities to create new‐generation structures with multiple applications. Covalently cross‐linked approaches are a ground‐breaking strategy for the formation of homo or heterostructures made by design. However, the covalent assembly of transition metal dichalcogenides flakes is relatively underexplored. Here, a simple covalent cross‐linking method to build 2H‐MoS2–MoS2 homostructures is described, using commercially available bismaleimides. These assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…, franckeite and few-layer FePS 3 ) 97,121 and also allowed the construction of 2D homo and heterostructures. 122,123 The mild conditions of this type of chemistry make it useful for obtaining MoS 2 –DNA bioconjugates, 124 or to tailor the electronic properties of field-effect transistors by direct on-device chemistry. 125…”
Section: Covalent Chemistry Of 2d Materials: the Challenge Of Charact...mentioning
confidence: 99%
“…, franckeite and few-layer FePS 3 ) 97,121 and also allowed the construction of 2D homo and heterostructures. 122,123 The mild conditions of this type of chemistry make it useful for obtaining MoS 2 –DNA bioconjugates, 124 or to tailor the electronic properties of field-effect transistors by direct on-device chemistry. 125…”
Section: Covalent Chemistry Of 2d Materials: the Challenge Of Charact...mentioning
confidence: 99%
“…In this case, the soft nucleophilicity of S atoms allows the click integration of the molecular components through a Michael addition under very mild conditions. [281] This method has been particularly appealing for the Pérez's group, since further click chemistry approaches have been explored, for example, for either the covalent cross-linking of different flakes of 2H-MoS 2 through bismaleimide reagent, [290] the linkage of graphene to reach 2D/2D heterostructures, [291] or the formation of succinimide polymer adlayers covalently connected to 2H-MoS 2 by adding a basic reagent (rather than the molecular monolayer of maleimide clicked in absence of base). [292] Lastly, a fashionable way to overcome the inherent inner reactivity of 2H-TMD-mainly attributed to its neutral charge state that difficult electron transfer-is by employing the so-called phase transition engineering approach.…”
Section: Covalent Functionalization Of Tmcsmentioning
confidence: 99%
“…With this protocol, it is possible to obtain a highly efficient covalent attachment under very mild conditions, without transformation of the 2H-MoS 2 phase to the more reactive 1T-MoS 2 phase. 17,18 The use of these molecules for the functionalization of the 2H-MoS 2 phase has been proved useful with other transition metal dichalcogenides, 16 to decorate naturally occurring van der Waals heterostructures, 19 interconnect flakes, 20 and more recently for the formation of a graphene-MoS 2 covalent heterostructure where the electronic properties are dominated by the molecular interface. 21 Palma and co-workers have shown that the reaction is useful to obtain MoS 2 -DNA bioconjugates.…”
Section: Introductionmentioning
confidence: 99%